Development of Vibrating Headphones to Help Student with Deaf Disabilities in Android-Based Lectures - Rara Ajeng Pratiwi; Mega Iswari; Setia Budi; Zulmiyetri Zulmiyetri; Retno Triswandari; Arisul Mahdi; Gaby Arnez (Universitas Muhammadiyah Enrekang, 2024)
This research is motivated by the issues identified in the field concerning deaf students who face difficulties in obtaining auditory information. This challenge arises due to the communication format during the learning process that predominantly utilizes oral language. Therefore, the researcher developed Vibrating Headphones with the aim of facilitating deaf individuals in acquiring one-way communication through text. This study employed the Research and Development (R&D) method with the 4D development model (Define, Design, Development, and Dissemination). The prototype developed was validated by four experts, including experts in deaf disabilities, electrical engineering, adaptive technology, and IT. Additionally, user testing was conducted to assess the practicality of the prototype among four deaf students in the Special Education Department at UNP. The validation results by the four experts yielded an average score of 88.75%, indicating a very valid criterion. Meanwhile, the practicality test results by the four deaf individuals produced an average score of 76.75%, meeting practical criteria. Based on these validation and practicality tests, valuable feedback and comments were received from both experts and users.